PERANCANGAN PERBAIKAN KUALITAS LAYANAN E-COMMERCE : STUDI PELANGGAN JAKARTA - Rahmad Rezeki (Universitas Mercu Buana, 2018)
This study aims to measure the level of service quality and design of services quality improvement for e-commerce B to C (Business to Customer) and C to C (Customer to Customer) based on the perception of Jakarta customers. This research was conducted on Lazada and Blibli customers for B to C and Tokopedia and Bukalapak for C to C in Jakarta. The method used is eservqual method with 8 dimensions that is fulfillment, reliability, responsiveness, information, customer service, security, website design and empathy. Importance Performance Analysis (IPA) and Quality Function Deployment (QFD) methods for drafting proposals for improving service quality. The results of this study found that there is a gap in each dimension that is fulfillment: -0.55, reliability: -0.54, responsiveness: -0.76, information: -0.58, customer service: -0.75 , security: -0.60, website design: 0.47 and empathy: -0.68. The IPA results show that there are 24 quality attributes that must be corrected immediately with a proposed improvement plan that is the management of website content, procedures for updating and installing website content, information on the website integrated with order handling processes, customer service management, customer complaint service procedures, standards customer communication, integrated order handling management, optimization and efficiency of order handling processes, return procedures, customer data management, security of transaction processing and customer service media development. .